Membrane Processes for Direct Carbon Dioxide Capture From Air: Possibilities and Limitations - Castel, Christophe; Bounaceur, Roda; Favre, Eric (Frontiers in Chemical Engineering, 2021)
Direct capture of CO2 from air (DAC) shows a growing interest for greenhouse gases mitigation but remains controversial among the engineering community. The high dilution level of CO2 in air (0.04%) indeed increases the energy requirement and cost of the process compared to carbon capture from flue gases (with CO2 concentration around 15% for coal power plants). Up to now, solid sorbents (functionalized silica, ion exchange resins, MOF’s...) have been proposed to achieve DAC, with a few large scale demonstration units. Gas-liquid absorption in alkaline solutions is also explored. Besides adsorption and absorption, membrane processes are another key gas separation technology but have not been investigated for DAC up to now. The objective of this study is to explore the separation performances of a membrane unit for CO2 capture from air through a generic engineering approach. The role of membrane material performances and the impact of process operating conditions on energy requirement and module production capacity are investigated. Guidelines on the possibilities and limitations of membranes for DAC are finally proposed.